Scenarios of temporal environmental alterations and phytoplankton diversity in a changing bay in the East China Sea - Wang, Yu; Wang, Weibo; Huang, Yaqin; Chang, Lin; Tang, Xiaoming; He, Xuebao; Lin, Hui (Frontiers in Marine Science, 2023)
In the context of global change, the stressors of warming and eutrophication have significant ecological implications in coastal waters. In order to examine the diversity of phytoplankton and its relationship with water quality, we conducted a survey of phytoplankton community compositions and their correlation with environmental changes over four seasons in a eutrophic bay located in the East China Sea. Through a systematic analysis, we identified diatoms and dinoflagellates as the primary dominant groups, with the species Skeletonema costatum, Skeletonema marinoi, Biddulphia sinensis, Thalassiosira eccentrica, Leptocylindrus danicus, Coscinodiscus oculus-iridis, Coscinodiscus jonesianus, and Chaetoceros knipowitschi as the most abundant species in all seasons. Significant seasonal alterations were observed in both environmental settings and phytoplankton species richness, dominance, and abundance. The phytoplankton community varied in its response to diverse aquatic environments and was principally affected by temperature, silicic acid concentrations, and suspended solids. Elevated temperatures were found to promote an increase in phytoplankton abundance. However, no clear evidence of diatom and dinoflagellate succession in relation to N:P ratio was observed across seasons. Water quality analysis illustrated that the majority of the study area exhibited a mid-eutrophic with severe organic pollution. The abundance of phytoplankton was significantly influenced by eutrophication and organic pollution. The accelerated warming process related to coastal nuclear power plants and nutrient regime alterations significantly affect the temporal shift of the phytoplankton community. These findings contribute valuable insights into the effects of eutrophic environments on the structure of phytoplankton communities in coastal aquatic systems.